Teknik Pembuatan Pledoi dan Memori Banding di Rumah Tahanan Negara Kelas I Surakarta - Kurnianingsih, Marisa; Hananto, Avip Rusdi; Saputra, Cahya Handy; Iksan, Muchamad (CV. Edutechnium Indonesia, 2024)
A plea is a form of defense carried out by the defendant and his legal advisor containing responses relating to the demands or accusations of the public prosecutor, as well as matters that can mitigate the sentence and truths that support the defendant. This is regulated in Article 182, paragraph (1) of the Criminal Procedure Code. A plea, also known as a defense, is made in writing and read out during the trial. The purpose of the defendant in filing a plea is as a request to be granted a verdict of acquittal from all legal charges or to ask for leniency in sentence. Apart from the plea, after the case is decided, the defendant still has the right to take legal action in order to achieve justice, namely an appeal. The appeal is carried out with the aim of re-examining the case that has been decided by the judge at the first-level court, whether it is in accordance with the rules or whether there are irregularities in the first-level decision. This community service activity helps defendants to provide an understanding of the rights that defendants are entitled to in criminal justice through pleadings and legal appeals. This activity takes the form of legal empowerment, where defendants in the Surakarta Class I Detention Center are taught how to prepare pleadings and appeal memorandums properly and correctly in order to achieve the fairest possible justice and to better understand the demands of the public prosecutor and the first-level judge's decision.